Confirmation on Status of Omotemnus miniatocrinitus Chevrolat (Coleoptera: Dryophthoridae) in Snakefruit Growing Areas - Rangga Arinta Wisastra; Edhi Martono; Suputa Suputa (Jurnal Perlindungan Tanaman Indonesia, 2017)
-